The Digital Economy Booster the Growth of Micro, Small and Medium Enterprises in Ambon City - Maryam Sangadji; Jolyne Myrell Parera; Yuyun Yuniarti Layn (Institute of Computer Science (IOCS), 2022)
The role of digitization in developing MSMEs in the city of Ambon is a very important factor in increasing product competitiveness. The purpose of this study is to (1) obtain an overview of digital economic growth in Ambon City, (2) determine the benchmarking of the digital economy on Economic Growth in Ambon City, and (3) identify and analyze the main obstacles and keys to startup success, (4) create a development roadmap e-commerce within 1-2 years. The analysis of this study used a qualitative method. The results showed that (1) the growth of MSMEs in Ambon city grew through the intervention of the OPD (Regional Apparatus Organization), the private sector, Bank Indonesia Maluku Representatives, and community members who are members of Maluku Dagang Online. (2). Benchmarking strategy can be done with SWOT analysis to implement future strategies for superior products based on the short, medium, and long term. (3). MSME start-ups use the offline system more than the online system.